ANALYSIS MATHEMATICS LEARNING DIFFICULTIES IN ELEMENTARY SCHOOL (International Conference on Elementary Education, 2018)
This study aims to: 1) Explain the categories of mathematics learning difficulties (MLD) in primary schools, 2) describe the characteristics of learners experiencing mathematics learning difficulties (MLD) in primary schools, 3) Explain the factors causing mathematics learning difficulties ( MLD) in primary school students. The research method used is descriptive qualitative. The research design used is referring to the descriptive research steps of case study. The subjects of the study were teachers and students at SDN 1 Kadugede, sub-district Kadugede, SDN 2 Ciporang, sub-district Kuningan and SDN 3 Susukan, sub-district Cipicung, all schools are located in Kuningan District, West Java. Data collection techniques used are observation, interview and study documentation. Data analysis used refers to the analysis of qualitative research data. The results showed that mathematics learning difficulties (MLD) experienced by students in SDN 1 Kadugede, SDN 2 Ciporang and SDN 3 Susukan, included in MLD category related to children's difficulties in basic of mathematics. The characteristics of learners who experience mathematics learning difficulties (MLD) in SDN 1 Kadugede, SDN 2 Ciporang and SDN 3 Susukan, are divided into 1) weak in the development of mathematical concepts; 2) confusion in interpreting certain signs and symbols; 3) weak in the multiplication; 4) weaker in numeracy and often frustrating; 5) are not able to determine which one is the right way to solve a problem; 6) worksheet look garbled; 7) difficult to read and interpret the word problems; 8) are not able to determine how to resolve the problem, 9) does not use math skills taught at school in everyday life. In addition to the characteristics that become the general characteristics of learners who experience mathematics learning difficulties (MLD) there are several factors that cause mathematics learning difficulties (MLD), namely: 1) weakness of concentration; 2) Low motivation; 3) lack of learning readiness; 4) low self-esteem; 5) a mindset that is not ragged and not systematic; 6) lack of attention from parent.